Beyond race, sex, and sexual orientation : legal equality without identity / Sonu Bedi, Dartmouth College. - Bedi, Sonu (Cambridge University Press, 2013)
The conventional interpretation of equality under the law singles out certain groups or classes for constitutional protection: women, racial minorities, and gays and lesbians. The United States Supreme Court calls these groups 'suspect classes'. Laws that discriminate against them are generally unconstitutional. While this is a familiar account of equal protection jurisprudence, this book argues that this approach suffers from hitherto unnoticed normative and political problems. The book elucidates a competing, extant interpretation of equal protection jurisprudence that avoids these problems. The interpretation is not concerned with suspect classes but rather with the kinds of reasons that are already inadmissible as a matter of constitutional law. This alternative approach treats the equal protection clause like any other limit on governmental power, thus allowing the Court to invalidate equality-infringing laws and policies by focusing on their justification rather than the identity group they discriminate against.